Gonadotrophic hormone and reinforcement sensitivity systems in women with premenstrual dysphoric disorder - Ko, Chih‐Hung; Long, Cheng‐Yu; Yen, Cheng‐Fang; Chen, Cheng‐Sheng; Wang, Peng‐Wei; Yen, Ju‐Yu (Psychiatry and clinical neurosciences, 2014)
Aim Behavior inhibition and behavior approach system (BIS/BAS) determine the sensitivity to aversion and rewarding stimuli, respectively. This study aimed at evaluating the BIS/BAS of premenstrual dysphoric disorder (PMDD) and effect of estrogen and progesterone on the BIS/BAS. Methods Women with PMDD without treatment and control subjects were recruited from the community. The PMDD diagnosis was based on psychiatric interviewing and the result of two‐menstrual‐cycle follow up. A total of 67 women with PMDD and 75 control subjects were recruited and entered the final analysis. They were evaluated with BIS/BAS scale and for estrogen and progesterone levels in both premenstrual and follicular phases. Results The results revealed that BAS score was higher among women with PMDD in both premenstrual and follicular phases. Progesterone level negatively correlated with fun‐seeking, and its change in the menstrual cycle also negatively correlated to a change in fun‐seeking score among women with PMDD. Women with PMDD had a higher score in BIS in the premenstrual phase and the BIS score correlated to depression, anxiety, and hostility among them. Conclusion These results suggest reward sensitivity of women with PMDD is vulnerable to the effect of progesterone change in the menstrual cycle. Furthermore, the sensitivity to aversive stimuli plays an important role involving core symptoms of PMDD. The reinforcement sensitivity of PMDD deserves further detailed study.